Natural sweetener-based herbal mangrove coffee (Avicennia marina) formulation as a local functional beverage innovation - Sumartini Sumartini; Nirmala Efri Hasibuan; Kurnia Sada Harahap; Evi Maya Sari; Agus Setiyoko (Aurelia Journal, 2026)
Herbal coffee based on local natural ingredients has the potential to become a functional beverage innovation with high nutritional and bioactive value. This study aimed to formulate and evaluate the physical, chemical, and sensory characteristics of mangrove herbal coffee (Avicennia marina) using four types of natural sweeteners: palm sugar (GS), coconut sugar(GA), honey (GM), and refined sugar(GP). The herbal coffee powder was prepared from A. marina fruit through soaking, drying, and roasting at 120–150°C, followed by blending with each sweetener formulation. Analyses included physical parameters (color, solubility, moisture content, bulk density), chemical composition (total phenolics, total sugar, pH), proximate composition (carbohydrate, protein, fat, and energy), and sensory evaluation using a 9-point hedonic scale. The results indicated that sweetener type significantly affected product quality. The palm sugar formulation showed the highest total phenolic content (16.87 mg GAE/g) and the most balanced taste, whereas the honey formulation had the highest total sugar and energy values (34.77 g/100 g; 191.7 kcal/100 g). Sensory evaluation revealed that mangrove coffee with palm sugar and coconut sugar achieved the highest preference scores for color, aroma, and taste (mean scores 7.2–7.4). Formulations with palm-based sweeteners exhibited the best balance between physical quality, bioactive content, and consumer acceptability. This study highlights the potential of A. marina as an innovative local raw material for functional beverage development that supports sustainable utilization of coastal resources.